Volume 3: Heat Transfer, Parts a and B 2006
DOI: 10.1115/gt2006-90754
|View full text |Cite
|
Sign up to set email alerts
|

Separated Flow Transition on an LP Turbine Blade With Pulsed Flow Control

Abstract: Flow measurements were made on a highly loaded low pressure turbine blade in a low-speed linear cascade facility. The blade has a design Zweifel coefficient of 1.34 with a peak pressure coefficient near 47% axial chord (mid-loaded). Flow and surface pressure data were taken for Rec = 20,000 with 3% inlet freestream turbulence. For these operating conditions, a large separation bubble forms over the downstream portion of the blade suction surface, extending from 59% to 86% axial chord. A Single-element hotfilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Much work has gone into studying the equilibrium effects of flow control, airfoil design, and the general properties of flow around airfoils at these lower Reynolds numbers. Even so, the short term transient and detailed unsteady effects are not as widely documented, though material does exist ( [1,2,3]). For MAV applications, these time dependent effects of flow control become very important, as oscillations and spikes in the non-dimensional forces C l , C d , and C m can cause pitching and plunging.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has gone into studying the equilibrium effects of flow control, airfoil design, and the general properties of flow around airfoils at these lower Reynolds numbers. Even so, the short term transient and detailed unsteady effects are not as widely documented, though material does exist ( [1,2,3]). For MAV applications, these time dependent effects of flow control become very important, as oscillations and spikes in the non-dimensional forces C l , C d , and C m can cause pitching and plunging.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of this facility is given by Bons et al (2008b). The cascade tunnel includes a wake generator consisting of carbon-fiber tubes mounted on a motor-driven chain assembly in order to imitate the effects of a rotor.…”
Section: Low-speed Cascade Tunnel and Instrumentationmentioning
confidence: 99%
“…The L1A blade section is characterized by an aft-loaded pressure distribution with a base separation line beginning near 57% of the axial chord C x (C x = 0.143 m) and continuing to the trailing edge (Bons et al 2008b) for a Reynolds number of 21,000 based on axial chord. With a profile designed by the US Air Force Research Laboratory, the blade had a true chord measurement of 0.156 m and span of 0.38 m. Flow control is employed on the blade in the form of vortex generator jets, an active technique for delaying separation on low-pressure turbine blades.…”
Section: Introductionmentioning
confidence: 99%
“…Since the profile is supposed to be applicable over a wide Reynolds number range, an active flow control method was favoured. Comparing different active methods, several authors like Bons et al [6] and Cerretelli and Kirtley [7] reported that unsteady excitation of the boundary layer flow is much more efficient than, for example, steady blowing. Cerretelli and Kirtley [7] achieved with fluidic oscillators a 60% reduction of injection momentum combined with a 30% reduction in blowing power compared to optimal steady blowing in a diffuser test rig.…”
Section: Introductionmentioning
confidence: 99%